Analisis Personal Branding Motivasi Islami Pada Akun Instagram @ISTIQMHHHHHHH - Ferdiansyah, Rifki Ahmad; Taufik, Reza Rizkina (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Along with the current development of the internet, social media has become a broad and easy-to-use means for people to interact attractively and can be accessed anywhere and at any time. Through social media, someone can express themselves, share thoughts and knowledge, increase relationships or networks, and build personal branding, such as on the @istiqmhhhhhhh account. This research aims to see the fact that Instagram can build a personal personal branding through Islamic motivations on social media. Istiqomah is a Muslim content creator who builds personal branding on her Instagram account through Islamic motivational content and productivity as a Muslim. This research is a qualitative descriptive research assisted by symbolic interaction theory which uses data sourced from in-depth interviews during online observations. The results of this research are Istiqomah's strategy, type of content, and consistency in building its personal branding on Instagram social media. This requires someone to be able to adapt to changes and remain relevant in building personal branding.